Performance of active electrical earthing systems: background and methodology - Hamzah, M. N.; Gomes, C.; Afiq, M.; Ab Kadir, M. Z. A. (IEEE, 2023)
An effective earthing system with new earth resistance reducing agents (ERRA) and purpose-made electrode configuration has been discussed as Active Electrical Earthing System (AEES). This paper is a precursor of a research work that will be presented consequently. Conventional earthing systems pose undefeatable challenges in some instances due to the expansion of system loads, compactness of sites and environmental degradation of the earthing systems. The development of new and more sophisticated electrical systems requires earthing systems that are effective, durable and site-specific. In urban areas with high population density and also at sites of pathological landscapes (such as tower sites in mountain terrains, and lightning protection of urban buildings), the availability of large soil masses for effective earthing systems is a significant challenge. Rapid material degradation of earthing rods is a significant issue in corrosive atmospheres, where both air quality and soil composition may contribute to the aggressiveness of the surrounding electrode material. Thus, more robust, and site-effective earthing technologies that may mitigate these drawbacks, have a high demand on the market front at present. This paper discusses the existing systems and methodology for a new system.